Innovation project – SafeBike - Ganchev, Stoyan Hristov (Yearbook Telecommunications, 2021)
This article presents a student project finalist in the annual competition for the TWENTY-FIRST STUDENT SECTION - US’21 May 15 - 16, 2021. The development is a full-featured model-prototype of an electronic smart device supporting safety when riding a bicycle. It consists of hardware and software implementation.